The Migration of Educational Software "Edu Tic" to a FLOSS Platform Accesible Via - Alderete, Romina; Marino, Sonia I.; Primorac, Carlos; Escalante, Jaquelina; Godoy, Maria Viviana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2012)
The paper presents an educational software migration for teaching-learning activities ofprimary school level in the area of Spanish Language. The work consists of the following sections.The first section presents a nover view to contextualize the work and the results obtained before migration software. The second section summarizes the methodology applied, based on Software Engineeringand Educational Software. The third section describes product features. Finally, some conclusions are presented, emphasizing that this software contributes to primary education. It was generated asolution to specific need of the education system, in order to contribute to the development of the context through the implementation software product of social impact and value added in relation to ICT in society.